2010
DOI: 10.1109/lawp.2010.2054060
|View full text |Cite
|
Sign up to set email alerts
|

A Singly Fed Rectangular Dielectric Resonator Antenna With a Wideband Circular Polarization

Abstract: Article:Sulaiman, M.I. and Khamas, S.K. (2010) ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…The literature based on circular polarization has already been discussed in previous section. Apart from this, some other characteristics say wideband, [136][137][138][139][140][141][142][143][144][145][146][147][148][149][150][151][152][153] dualband/ multiband [154][155][156][157][158] including circular polarization have also been reported in literature. This is also being discussed in this section.…”
Section: Circular Polarization With Other Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature based on circular polarization has already been discussed in previous section. Apart from this, some other characteristics say wideband, [136][137][138][139][140][141][142][143][144][145][146][147][148][149][150][151][152][153] dualband/ multiband [154][155][156][157][158] including circular polarization have also been reported in literature. This is also being discussed in this section.…”
Section: Circular Polarization With Other Characteristicsmentioning
confidence: 99%
“…Sulaiman and Khamas 143 have suggested a single feed mechanism with three metallic strips on a half loop antenna for 7% CP bandwidth, which has been again improved to 13% just by adding concentric parasitic open half loop. Sulaiman and Khamas 144 have demonstrated that, by shifting the square spiral shaped feed from center to the right of the DRA surface supported mode from TE y 111 to TE x 111 mode and yields a CP bandwidth of 7%. Khalily et al 145 have achieved 600MHz bandwidth CP rectangular DRA.…”
Section: Circular Polarization With Widebandmentioning
confidence: 99%
“…In the public literature, many feeding techniques have been proposed to achieve circular polarization [8] such as exciting the DRA with a dual-coaxial probe, dual-conformal strip or with parasitic strips, rotated sequential and aperture feeds. So far there was a number of different element configurations published, including semi-elliptical DR with a hollow elliptical cylinder [9], radiating with a stair-shaped DR [10] and feeding with a square spiral strip [11]. Although most of the configurations mentioned show good performance to generate circular polarization, achievable gain and bandwidth are still below the objectives for the 60 GHz millimeter wave band.…”
Section: Introductionmentioning
confidence: 99%
“…AR bandwidths of 3.91% and 2.2% have been achieved for cylindrical DRA excited by a cross-slot [12], and slotcoupled structure [13], respectively. A conformal square spiral strip exciting the cylindrical DRA with a 4.3% CP bandwidth has been reported in [14]. Since the traveling-wave current distribution changes slowly with frequency, a wider CP bandwidth is expected.…”
Section: Introductionmentioning
confidence: 99%
“…Since the traveling-wave current distribution changes slowly with frequency, a wider CP bandwidth is expected. Such a feeding method has been reported in [15], where a CP bandwidth of 7% has been achieved using a spiral strip to excite a rectangular DRA.…”
Section: Introductionmentioning
confidence: 99%